Beyond death : the mystical teachings of ʻAyn al-Quḍāt al-Hamadhānī - Papan-Matin, Firoozeh. (Islamic History and Civilization, 2010)
The twelfth-century Iranian mystic 'Ayn al-Quḍāt al-Hamadhānī (d. 1131) wrote vividly of his explorations of death as a state of consciousness which he experienced while alive. This state and his visions of Doomsday and the innumerable non-corporeal worlds that lie past the world of matter confront him with paradoxical realities that upset the notional understanding of faith. The present book concerns itself with a discussion on the subject of death as it is viewed by one of the defining mystic scholars of medieval Iran. Based on medieval manuscripts and primary sources in classical Persian and Arabic, this book explores the significance of this important Iranian mystic and his insights on the nature of reality in light of death.